Labelling of corn as forage for ruminants using isotope 15N. Issue 1 (November 2021) - Sugoro, I; Maharani, Y; Hanani, M; Ansori, D; Wahyudiyanto, H; Rizqikah, A; Dasumiati,; Wahyono, T; Firsoni,; Sasongko, W T; Fahmi, N; Flatian, A N
Abstract: In vitro and in vivo testing for ruminant feed efficiency can be done by utilizing the stable isotope Nitrogen-15 ( 15 N) as a tracer. Feed can be traced by labeling the forage using isotope 15 N. Feed crops are labeled using an isotope 15 N-enriched fertilizer. The critical thing to note is to know the content of isotopes 15 N in the part of forage feed plants that have been labeled. This research aims to know the effect of urea fertilizer on the percent of atom excess 15 N on corn. Corn are labeled using urea enriched with isotopes 15 N in the form of urea fertilizer (10% excess atom 15 N) with different doses (0-200% recommended urea dose). As a control used corn plants given urea fertilizer is not labeled 15 N. The results showed that corn forage feed was successfully labeled and correlated with the dose of fertilizer. The range of atom excess 15 N was 4.28 – 6.99% in corn forage. Biomass production showed no significant difference between the dose of fertilization and control, but neither protein content. Based on data, the corn forage can be used for further testing.